Kontribusi Motor Educability terhadap Teknik Dasar Sepak Bola Siswa SD Negeri 2 Pasirwangi - Sidiq, Ilham Fajar; Imanudin, Iman; Zaky, Mohammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the contribution of motor educability to basic soccer techniques in students of SDN 2 Pasirwangi. This study used a quantitative descriptive correlational method with a cross-sectional approach, involving 35 12-year-old students selected through random sampling. The results showed that the measurement instruments for motor educability and basic soccer techniques were very valid and reliable, with validity values ​​of 0.940 and 0.998, and reliability of 0.999. The normality test showed that the data were normally distributed. The results of the correlation test showed a significant positive relationship between motor educability and basic soccer techniques, with a Pearson correlation value of 0.894 and a significance of 0.000. The results of the ANOVA test showed that the regression model predicting the contribution of motor educability to basic soccer techniques was significant, with an F value of 131.527 and a significance of 0.000. In conclusion, Motor educability significantly contributes to students' basic football technical abilities at SD Negeri 2 Pasirwangi, so motor learning abilities must be considered in the football learning and training process. Keywords ; Anova, Basic Soccer Techniques, Motor educability, Motor Skills